Metformin as a potential protective therapy against tuberculosis in patients with diabetes mellitus: A retrospective cohort study in a single teaching hospital - Chia‐Po Fu (Journal of Diabetes Investigation, 2021)
Abstract Aims/Introduction The convergence of tuberculosis (TB) and diabetes mellitus (DM) is a new challenge in Asia as a result of the rising prevalence of diabetes mellitus with higher TB infection rates, and also because diabetes mellitus itself enhances TB disease activity and consequently the spread of TB. We aimed to address the risk presented by diabetes mellitus for TB infection. Materials and Methods Patients with diabetes mellitus were retrospectively recruited. The baseline assessments included age, sex, body mass index, fasting blood glucose, glycated hemoglobin, urine albumin‐to‐creatinine ratio and estimated glomerular filtration rate. TB was determined by meeting the international classification of disease, for TB diagnosis and receiving anti‐TB treatment for at least 2 months. Results In total, 9,750 individuals with diabetes mellitus were recruited. The event rate of TB was 47 (0.48%). Younger age, lower proportion of men, higher fasting blood glucose and glycated hemoglobin values, and better renal function (estimated glomerular filtration rate and urine albumin‐to‐creatinine ratio) were observed in the metformin‐exposed groups. Old age and male sex were associated with higher TB infection risk on multivariate analysis. Metformin users had a significantly lower risk for TB infection, whereas insulin users had a higher risk for TB infection. However, glycemic status had no effect on TB infection risk. Conclusions This study provides clinical evidence from a survey of TB in individuals with diabetes mellitus. Old age, male sex and insulin use were risk factors for TB infection. Metformin remains the first choice of treatment for diabetes mellitus and has a potential protective effect against TB infection.